Strategic Review of Mobile Value-Added Services (M-VAS) Opportunity Based On Customer Satisfaction and Loyalty Criteria in Indonesia (The Indonesian Journal of Business Administration, 2013)
Today, the telecommunications industry in Indonesia is experiencing a relative decline in ARPU (Average Revenue Per User) resulting in lower income mobile telecommunications service providers. This situation reveals that income from conventional voice services will not be enough for the mobile telecom service providers to survive. To overcome this, mobile operators develop a Mobile Value-Added Services (M-VAS) as a source of new revenue and differentiation strategies. Therefore, this research aims to discuss strategies and investigate the use of M-VAS in order to examine the determinants of customer satisfaction and loyalty in Indonesia so it will have an impact on corporate earnings. The findings confirm that mobile browsing and social media are the most frequently used by mobile subscribers. In addition, it was also discovered that the trust did not significantly affect the loyalty and social value does not affect satisfaction significantly. The finding of insignificant trust is allegedly as a result of balance theft that occurred in 2011. Regardless of the government's role as regulator, customer trust will be achieved if the infrastructure overhaul and properly communicated to customers through advertising, sales force activity, and Customer Lifecycle Management (CLM). The proposed implementation plan in the form of a list of activities, resource requirements, and the calendar of events up to the year 2014 where the election will be held.Â Keywords: M-VAS, Loyalty, Satisfaction, Balance Theft